Elevated Serum Regulator of Calcineurin 2 is Associated With an Increased Risk of Non-Alcoholic Fatty Liver Disease - Fang, Xia; Wang, Hongya; Tan, Xiaozhen; Ye, Ting; Xu, Yong; Fan, Jiahao (Frontiers in Pharmacology, 2022)
Background: The promoting effect of the regulator of calcineurin 2 (RCAN2) in hepatic steatosis has been observed in animal studies. However, the association of RCAN2 with non-alcoholic fatty liver disease (NAFLD) in humans remains unclear. This study aimed to evaluate the expression of RCAN2 in the liver of mice with hepatic steatosis and in serum of NAFLD patients, and to explore the relationship between serum RCAN2 levels and NAFLD. Methods: The mRNA and protein expression of RCAN2 were detected by quantitative real-time PCR (qRT-PCR) and western blot. NAFLD was diagnosed by abdominal ultrasonography. Circulating RCAN2 levels were measured by ELISA kits. The relationship between serum RCAN2 levels and NAFLD was assessed. Results: qRT-PCR and western blot analysis showed that compared with the corresponding controls, the mRNA and protein expression of RCAN2 were significantly increased in the liver tissues of db/db and mice on a high fat diet. Serum RCAN2 levels were markedly elevated in NAFLD patients compared with non-NAFLD subjects. Binary logistic regression analysis showed that serum RCAN2 levels were significantly associated with NAFLD. Receiver operation characteristic (ROC) curve analysis showed that serum RCAN2 might act as a predictive biomarker for NAFLD (area under the curve [AUC] = 0.663, 95% CI = 0.623-0.702), and the serum RCAN2/ (AST/ALT) ratio displayed improved predictive accuracy (AUC = 0.816, 95% CI = 0.785-0.846). Conclusions: Elevated serum RCAN2 levels were associated with an increased risk of NAFLD. Serum RCAN2, especially the serum RCAN2/(AST/ALT) ratio, might be a candidate diagnostic marker for NAFLD.